Extended Dynamic Oligopolies with Flexible Workforce and Isoelastic Price Function - Matsumoto, Akio; Merlone, Ugo; Szidarovszky, Ferenc (Frontiers in Applied Mathematics and Statistics, 2016)
Single-product oligopolies without product differentiation are examined with linear production, production adjustment, flexible workforce and investment costs. The price function is assumed to be hyperbolic which makes the nonlinearity of the model much stronger than in the case of linear price function examined earlier in the literature. The best responses of the firms are determined which are not monotonic in contrast to the linear case. The set of all steady states is then characterized and in the case of a duopoly it is illustrated. The asymptotical behavior of the steady states is examined by using simulation. We analyze the effects of such costs on the industry dynamics and compare them to the prediction by the well known model with hyperbolic price function and no product adjustment and investments costs.